GENOTYPE POLYMORPHISMS OF NAT2 AND CYP2E1 GENES ASSOCIATED WITH DRUG INDUCED LIVER INJURY (DILI) IN INDONESIAN TUBERCULOSIS PATIENTS - Perwitasari, Dyah Aryani (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2016)
Â Â Â Â Â Â Â Currently, Indonesia is in the fifth rank of highest TB prevalence over the world. One of the TB problem is low patientsâ adherence due to the oral antituberculosis induced hepatotoxicity. Polymorphisms of NAT2 and CYP2E1 genes had important role in the isoniazid (INH)-induced hepatotoxicity. The aim of this study was to evaluate the polymorphisms profile of NAT2 and CYP2E1 genes associated with hepatotoxicity induced by INH.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â We used cohort design in Public Health Centers and Lung Clinics of Yogyakarta and Lampung. The inclusion criteria were adult subjects (> 18 yo), newly diagnosed TB and treated by oral antituberculosis, normal function of renal and live and willingness to participate in this study. Subjects were excluded when having positive reaction of Â HbsAg test, history of HIV and abnormality of renal and liver function. The SNPs of NAT2 and CYP2E1 were designed using IPlex method of DNA sequenom.Â Â Â Â Â Â Â Â Â Â Â Â Among 57 TB patients, we found 14 patients with higher INH serum concentration and experienced increase of ALT-AST. Subjects withÂ SNPs of rs 2070676, rs 1329149, rs 3813867, rs 6413432, rs 8192772, rs 2031920, rs 2515641, rs 8192775, rs 915908 ofÂ CYP2E1 Â experienced increase of ALT and AST. Subjects with SNPs Â of rs 1799930, rs1799931, rs1801279, rs1801280, rs1799929 , rs1208, rs1041983 of Â NAT2 are associated with the increase of ALT and AST.Â Â Â Â Â Â Â Â Â Â Â Â The polymorphisms of Â CYP2E1 and NAT2 may have a role in the mechanisms of INH induced DILI.Â Keywords: CYP2E1, NAT2, tuberculosis, isoniazid, Indonesia